STUDY OF THE FORMULATION OF SWEET SOY SAUCE FROM SMALL SHRIMP (Acetes erythraeus) TOWARD CONSUMER ACCEPTANCE - Azhari, David Akbar; Suparmi, Suparmi; Dahlia, Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The purpose of this study was to determine the level of consumer acceptance against the sweet soy sauce from small shrimp (Acetes erythraeus)added with caramelized sugar. The treatment given was the addition of caramelized sugar in different amounts, with 3 levels namely: U1 (50 gram of caramelized sugar), U2 (60 gram of caramelized sugar), and U3 (70 gram of caramelized sugar). The results showed that sweet soy sauce from small shrimp which was most preferred by consumers was obtained from U2 treatment (sweet soy sauce from small shrimp with the addition 60 grams of caramelized sugar). The U2 treatment had an average value very like and like of color (3.36) with the number of panelists 47.5% having criteria for blackish brown, aroma (2.84) with the number of panelists 92.5% having criteria for spice aroma and specific smell of small shrimp, flavor (3.40) with a number of panelists of 71.25% having taste criteria from the same specific spices and caramelized sugar and small shrimp, the thickness (3.47) with the number of panelists 65% had thick and compact criteria, meanwhile for the proximate value of water content, protein content, fat content, ash content, viscosity, and amino acids was 43.91%, 14.79%, 0.35%, 11.35%, 3.93%, and 4.92%, respectively. It can be seen that the sweet soy sauce of small shrimp with the addition of caramelized sugar has a very significant effect on the value of color, aroma, taste, and thickness.Keywords: Sweet soy sauce, small shrimp, caramelized sugar